Formulation And Evaluation Of Transdermal Patches Of 5-Fluorouracil For The Treatment Of Skin Cancer - Upadhyay, Manshi; maurya, Priyanka; Mishra, Jai Narayan (Journal of Neonatal Surgery, 2025)
The present study focuses on the formulation and evaluation of transdermal patches of 5-fluorouracil (5-FU) intended for the topical treatment of skin cancer, aiming to enhance localized drug delivery while minimizing systemic side effects. 5-FU, a potent antimetabolite used in chemotherapy, suffers from poor skin permeability and rapid metabolism when administered conventionally. To overcome these limitations, transdermal drug delivery offers a non-invasive and controlled release system that can maintain therapeutic drug levels at the site of action. Transdermal patches were prepared using solvent casting technique employing various polymers such as hydroxypropyl methylcellulose (HPMC), ethyl cellulose (EC), and polyvinyl alcohol (PVA) either alone or in combinations, along with suitable plasticizers like glycerol or polyethylene glycol (PEG 400). The prepared patches were subjected to a series of physicochemical evaluations including thickness, weight variation, folding endurance, surface pH, drug content uniformity, moisture content, water vapor transmission rate, and in vitro drug release studies using Franz diffusion cell. Among the different formulations, the patch containing HPMC:EC in a 2:1 ratio exhibited optimal physical properties and sustained drug release up to 24 hours, showing a cumulative drug release of over 85%, indicating a controlled release pattern. The in vitro permeation study demonstrated enhanced skin penetration, and FTIR studies confirmed no significant interaction between 5-FU and the excipients. The stability studies, conducted as per ICH guidelines, showed no significant changes in drug content and appearance over a period of three months. In conclusion, the formulated transdermal patches of 5-fluorouracil offer a promising alternative to conventional topical or systemic therapies for skin cancer by enabling localized, sustained delivery of the drug with improved patient compliance and reduced systemic toxicity..